MINDSET GROWTH SEBAGAI SOLUSI TEACHING PHOBIA DALAM PERSIAPAN MICROTEACHING MAHASISWA - Larasati, Dini Mutia; Saputri, Nadila Dwi; Anjani, Iva; Nia, Nia; Netriwati, Netriwati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study was motivated by the presence of anxiety or teaching phobia among students in facing microteaching activities, despite having adequate academic understanding. One of the factors assumed to influence this condition is growth mindset, which refers to the belief that abilities can be developed through effort and learning experiences. This study aims to examine the relationship between growth mindset and teaching phobia among students in preparation for microteaching. This research employed a quantitative approach with a correlational design. The participants consisted of 39 students, and data were collected using questionnaires that had been tested for validity and reliability. The data were analyzed using Pearson correlation with the assistance of SPSS. The results showed a significant relationship between growth mindset and teaching phobia, with a correlation coefficient of 0.515 and a significance value of 0.001. These findings indicate that growth mindset plays a role in shaping students’ emotional responses in teaching activities. Although theoretically expected to have a negative relationship, the results revealed a positive tendency, which can be interpreted as increased reflective awareness among students toward the learning and self-evaluation process, leading to higher sensitivity to mistakes and evaluation in the early stages of microteaching. Therefore, growth mindset has the potential to be developed as an approach to reduce teaching phobia, supported by appropriate learning strategies. ABSTRAK Penelitian ini dilatarbelakangi oleh masih ditemukannya kecemasan atau teaching phobia pada mahasiswa dalam menghadapi kegiatan microteaching, meskipun mereka telah memiliki pemahaman akademik yang memadai. Salah satu faktor yang diduga berperan adalah growth mindset, yaitu pola pikir yang memandang kemampuan sebagai sesuatu yang dapat dikembangkan melalui usaha dan pengalaman belajar. Penelitian ini bertujuan untuk mengetahui hubungan antara growth mindset dengan teaching phobia pada mahasiswa dalam persiapan microteaching. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian korelasional. Subjek penelitian berjumlah 39 mahasiswa, dengan teknik pengumpulan data menggunakan angket yang telah diuji validitas dan reliabilitasnya, serta dianalisis menggunakan uji korelasi Pearson dengan bantuan program SPSS. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara growth mindset dengan teaching phobia dengan nilai koefisien korelasi sebesar 0,515 dan nilai signifikansi sebesar 0,001. Temuan ini mengindikasikan bahwa growth mindset berperan dalam membentuk respons emosional mahasiswa dalam kegiatan mengajar. Meskipun secara teoritis diharapkan berkorelasi negatif, hasil penelitian menunjukkan kecenderungan hubungan positif yang dapat diinterpretasikan sebagai meningkatnya kesadaran reflektif mahasiswa terhadap proses belajar dan evaluasi diri, sehingga pada tahap awal pembelajaran dapat memunculkan kecemasan. Dengan demikian, growth mindset tetap berpotensi dikembangkan sebagai pendekatan dalam mengurangi teaching phobia dengan dukungan strategi pembelajaran yang tepat.